How to improve performance and prevent burnout in safety representatives - Dal Corso, Laura; Carluccio, Francesca; Scarcella, Malì; Bartolucci, Giovanni Battista; Bizzotto, Rosana; Vianello, Liviano; Magosso, Doriano; De Carlo, Nicola Alberto (La Medicina del Lavoro, 2019)
Background: The present work is part of a greater research project, aimed to examine Safety Representatives’ (SRs) role, twenty years after the appointment of this figure. Objectives: The study aims to investigate the role of some personal and organizational dimensions in the promotion of SRs’ well-being, in terms of reducing burnout and improving performance. Methods: The study involved 455 SRs operating in North East Italy. They completed a self-report questionnaire, regarding conflicts with co-workers, ethical conflict, training satisfaction, work engagement, performance, and burnout. Results: Structural equation models show that work engagement partially mediates (γ=-0.52, p